Spectrophotometric Determination of Vancomycin Hydrochloride in Pharmaceutical Preparations through Diazotization and Coupling Reactions - Hadi, Hind (Iraqi Journal of Science, 2023)
Two simple, sensitive, accurate and economic methods A and B have been developed for the quantitative estimation of vancomycin hydrochlorid (VHC) and its formulations using another two drug compounds as a coupling reagents.The proposed methods are based on a coupling reaction between VHC and diazotized procain (method A) or diazotized sulphacetamide sodium (method B) in alkaline medium to form intense yellow, water-soluble dyes that are very stable and have a maximum absorption at 447 and 439 nm for methods A and B respectively. Regression analysis of Beer’s law plots showed good correlation in the concentration ranges 1-28 and 1-45 μg ml-1 for methods A and B, respectively with a molar absorbtivity of 4.605×104 L mol-1cm-1 and 4.516×104 L mol-1cm-1, Sandell’s sensitivity of 0.032 g.cm-2 and 0.033 g.cm-2 for methods A and B respectively. Relative standard deviation (RSD%) were less than 2.9 for both methods.The methods were successfully applied to the determination of VHC in bulk drug and its formulations.